Big data : the essential guide to work life and learning in the age of insight - Viktor Mayer- Schonberger; Cukier, Kenneth (London John Murray, 2017)
We're just starting to reap the benefits: tracking vital signs to foresee infections, predicting building fires, anticipating the best moment to buy a plane ticket, seeing inflation in real time and monitoring social media in order to identify trends. But there is a dark side to big data. Will it be machines, rather than people, that make the decision? How do you regulate an algorithm? What will happen to privacy? Will individuals be punished for acts they have yet to commit In this groundbreaking and fascinating book, two of the world's most-respected big data experts reveal the reality of a new world and outline clear and actionable steps that will equip the reader with the tools needed for this next phase of human evolution.
Keywords: Computer Science